2018
DOI: 10.1108/bepam-12-2017-0119
|View full text |Cite
|
Sign up to set email alerts
|

Causal relationship between material price fluctuation and project’s outturn costs

Abstract: Purpose A section of project management literature attributes overruns to estimators’ deceit and delusion. An example of this is Flyvbjerg’s theorisation of strategic misrepresentation and optimism bias. To show that such a notion is not true entirely, the study elicits evidence relating to how costs of projects often fluctuate erratically as prices of construction materials change throughout contract cycle times. The purpose of this paper is to examine the causal relationships between persistent changes in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
(49 reference statements)
0
6
0
Order By: Relevance
“…Similarly, the currency in which project payment will be made is important. Contractors can be deterred where project's currency is known to be erratic in value and has had limited advantage in the international market, or where project is domiciled in currencies where contractor's business has no commercial value (Olatunji et al ., 2018).…”
Section: Client Attributes and Their Relationships With Project Outcomesmentioning
confidence: 99%
“…Similarly, the currency in which project payment will be made is important. Contractors can be deterred where project's currency is known to be erratic in value and has had limited advantage in the international market, or where project is domiciled in currencies where contractor's business has no commercial value (Olatunji et al ., 2018).…”
Section: Client Attributes and Their Relationships With Project Outcomesmentioning
confidence: 99%
“…Financial Shortfall [14,40] Community involvement [40,99] Labour strikes [88,105,110] Shortage of labour [72,110] lengthy bureaucratic processes [41,50,81,[111][112][113][114][115] Economic business cycles [6,112] Acquiring regulatory approvals [81,109] Exploitation [99,113] Global financial crisis [58,81] Delayed Payments [88,116,117] Delayed materials and equipment [118][119][120] High interest rates/ inflation [35,88,[121][122][123] Abandonment of Project [118] Machinery and Equipment failure [88,105] Transportation cost for labour, equipment and materials to and from site [70,124,125] Failure and availability of equipment [126] Price fluctuations [127][128][129] Shortage of skilled and unskilled labourer...…”
Section: Table 3 Critical Risk Group (Root Cause) -Socio-economical C...mentioning
confidence: 99%
“…Normative studies have reported the behaviours of construction contractors during bidding and project execution as though they are a linear process: rational, predictable, scientific and simplistic (Ansar et al, 2014;Flyvberg et al, 2003;Flyvbjerg et al, 2018;Green, 1989;Love and Ahiaga-Dagbui, 2018;Olatunji et al, 2018). However, Contractors bid for projects for different reasons: some rely on past and current experiences of themselves and others, some gamble by taking rational risks where competition is limited and success or failure is safe to admit, whilst others depend only on subjective instruments such as current workload, informal connections and sheer luck (Fadic, 2020;Loosemore and Richard, 2015;Shapira, 1995;Smith, 2017).…”
Section: Elements Of Contractors' Administrative Characteristics In B...mentioning
confidence: 99%
“…, 2003; Flyvbjerg et al. , 2018; Green, 1989; Love and Ahiaga-Dagbui, 2018; Olatunji et al. , 2018).…”
Section: Elements Of Contractors' Administrative Characteristics In B...mentioning
confidence: 99%